The LG and LGA’s Collaboration in SDGs Implementation of the Geopark of Sawahlunto City, Indonesia - Isabella; Safendri K Ragamustari; Desideria Cempaka Murti (Universitas Medan Area, 2023)
This article elucidates the significance of collaboration between the Local Government (LG) and the Local Government Association (LGA) in the Sustainable Development Goals (SDGs) implementation within Sawahlunto City Geopark, Indonesia that aims to explore the role of diverse stakeholders in shaping policy implementation in Indonesia, particularly in the context of Geopark tourism in Sawahlunto. The central issue at hand concerns how LGA can assist in surmounting challenges and bolstering Sawahlunto City's aspiration to elevate its status from a National Geopark to a UNESCO Global Geopark (UGG). This research employs theoretical frameworks and adopts a qualitative approach using the quadruple helix investigator model. Data collection was conducted through semi-structured interviews and the acquisition of information from primary and secondary sources, including Medium-Term Development Plan (RPJMD), Geopark documentation, Project Documents, and more. The research findings underscore the pivotal role played by UCLG ASPAC, as an LGA, in collaborating with LG to optimize the involvement of other stakeholders in advancing RPJMD, particularly in the realm of tourism aligned with SDG 11.4. Furthermore, this collaboration is crucial for aiding LG in realizing its aspiration to attain UGG status. Additionally, it emphasizes the imperative for regional governments with geopark potential to develop their regional assets.